2012
DOI: 10.1364/ome.2.001571
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high quality sub-micron Au gratings over large areas with pulsed laser interference lithography for SPR sensors

Abstract: Metallic gratings were fabricated using high energy laser interference lithography with a frequency tripled Nd:YAG nanosecond laser. The grating structures were first recorded in a photosensitive layer and afterwards transferred to an Au film. High quality Au gratings with a period of 770 nm and peak-to-valley heights of 20-60 nm exhibiting plasmonic resonance response were successfully designed, fabricated and characterized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The total processed area depends on the beam intensity and coherence length of the laser and can be up to dozens, or even hundreds of square centimeters. The technology is much cheaper and simpler than electron beam lithography and can be used for manufacturing SPR sensor structures [18, 19]. In previous studies, we have shown that IL with the use of chalcogenide photoresist is a promising technology for the formation of one- and two-dimensional submicron periodic structures on the surface of semiconductors and dielectrics [20].…”
Section: Methodsmentioning
confidence: 99%
“…The total processed area depends on the beam intensity and coherence length of the laser and can be up to dozens, or even hundreds of square centimeters. The technology is much cheaper and simpler than electron beam lithography and can be used for manufacturing SPR sensor structures [18, 19]. In previous studies, we have shown that IL with the use of chalcogenide photoresist is a promising technology for the formation of one- and two-dimensional submicron periodic structures on the surface of semiconductors and dielectrics [20].…”
Section: Methodsmentioning
confidence: 99%
“…Today, there are several techniques of forming a diffraction grating on the semiconductor substrate, namely, the laser-induced periodic surface structures [4], extreme ultraviolet lithography [5], electron beam lithography [6], ion beam lithography [7], nanoimprint technology [8], pulsed laser interference lithography [9], and laser interference lithography [10, 11]. The latter is well known and relatively cheap method that allows to form a planar periodicity on large areas.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate was then exposed to form periodic nanopore patterns in a square array by using laser interference lithography. [35][36][37] The interference lithography systems and processes used in this study were especially developed for the large-area (i.e., full wafer-scale) nanopatterning, as reported earlier. 12,[38][39][40][41][42][43] In this work, the nanopore patterns of two different periods (500 and 900 nm) were prepared by using a He-Cd laser of a wavelength of 325 nm (IK3501R-G, Kimmon Koha Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%